Bank supervision Russian style: rules versus enforcement and tacit objectives - Sophie Claeys; Gleb Lanine; Koen Schoors (Bank of Finland, Institute for Economies in Transition (BOFIT), 2005)
We focus on the con.ict between two central bank objectives individual bank stability and systemic stability.We study the licensing policy of the Central Bank of Russia (CBR) during 1999.2002.Banks in poorly banked regions, banks that are too big to be disciplined adequately, and banks that are active on the interbank market enjoy protection from license withdrawal, which suggests a tacit concern for systemic stability.The CBR is also found reluctant to with- draw licenses from banks that violate the individual's deposits-to-capital ratio as this conflicts with the tacit CBR objective to secure depositor confidence and systemic stability.
URN:NBN:fi:bof-201408071913
Keywords: G2; N2; E5; 330; Bank supervision; bank crisis; Russia